Study on Binding of Ferrous Ions by Methi Stem - Farroqui, Mazahar; Kotharkar, Sandeep (Asian Journal of Chemistry, 2010)
The presence of heavy metals such as Cu2+, Pb2+, Cd2+, Hg2+ and Fe2+ in waste water has been a matter of considerable concern in recent years because of their toxic properties. There are various methods such as precipitation, adsorption, ion exchange, etc. available to remove them from the effluent but all these methods are comparatively expensive. These heavy metals can be removed by using cheap agricultural waste products. In this communication use of stem of Fenugreek Methi ( Trigonella foenum graecum) for binding of Fe2+ ions has been investigated. The effect of pH, temperature and contact time has been thoroughly studied.